The A179L Gene of African Swine Fever Virus Suppresses Virus-Induced Apoptosis but Enhances Necroptosis - Jun Shi; Wei Liu; Miao Zhang; Jing Sun; Xiulong Xu (Viruses, 2021)
A179L, a non-structural protein of African swine fever virus (ASFV), is capable of suppressing apoptosis by binding the BH3 domain of the pro-apoptotic Bcl-2 family proteins via a conserved ligand binding groove. Our present study aims to determine if A179L affects necroptosis, the second form of programmed cell death induced by DNA and RNA viruses. Here we report that A179L enhanced TNF-α or TSZ (TNF-α, Smac, and Z-Vad)-induced receptor-interacting protein kinase (RIPK1), RIPK3, and mixed lineage kinase domain like peudokinase (MLKL) phosphorylation in L929 cells, a murine fibrosarcoma cell line. Sytox green staining revealed that A179L significantly increased the number of necroptotic cells in TSZ-treated L929 cells. Using human herpes simplex virus 1 (HSV-1) to model DNA virus-induced cell death, we found that A179L blocked the HSV-1-induced cleavage of poly (ADP-ribose) polymerase (PARP), caspase 8, and caspase 3 and decreased the number of apoptotic cells in HSV-1-infected IPEC-DQ cells, a porcine intestinal epithelial cell line. In contrast, A179L transfection of IPEC-DQ cells enhanced HSV-1-induced RIPK1, RIPK3, and MLKL phosphorylation and increased the number of necroptotic cells. Consistently, A179L also suppressed apoptosis but enhanced the necroptosis induced by two RNA viruses, Sendai virus (SeV) and influenza virus (IAV). Our study uncovers a previously unrecognized role of A179L in regulating cell death and suggests that A179L re-directs its anti-apoptotic activity to necroptosis.